2007
DOI: 10.1111/j.1471-6712.2007.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and resiliency in Swedish families

Abstract: A longitudinal research project began in 1993 of Norwegian, Swedish and American mothers' perception of her family's dynamics and adaptation during childbearing and childrearing. Results indicated that Swedish mothers adapted better than other mothers. In 2003, a mixed design study was conducted with original Swedish mothers that aimed to describe the experience of motherhood, the meaning mothers attached to events in their lives that made adaptation necessary, and ways in which they achieved adaptation. Fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The families’ capability for resilience in a changed life situation in this study was favoured by positive beliefs, family roles, family function, and communicative problem-solving abilities [60]. Similar to Walsh [61], we interpreted the results and identified three components that support our theoretical assumption and form family resilience: belief systems, organizational patterns, and communication processes.…”
Section: Discussionsupporting
confidence: 52%
“…The families’ capability for resilience in a changed life situation in this study was favoured by positive beliefs, family roles, family function, and communicative problem-solving abilities [60]. Similar to Walsh [61], we interpreted the results and identified three components that support our theoretical assumption and form family resilience: belief systems, organizational patterns, and communication processes.…”
Section: Discussionsupporting
confidence: 52%
“…), educational level (Lederman & Weis ), whether or not the pregnancy was planned (Visger ), employment status (Kiehl et al. ), level of income (Lederman & Weis ) and social characteristics such as social support (Choi ; Mercer ; Serçekuş & Mete ) and family or spouse support (Lederman & Weis ). A study conducted in Turkey found that women who were highly educated, were employed, had a planned pregnancy, had knowledge about the pregnancy process, had a high income level and had social security adapted to pregnancy and IMR better than those who did not (Demirbaş & Kadıoğlu ).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors may influence adaptation to pregnancy and the motherhood role in pregnant women (Lederman & Weis 2009; Serc ßekus ß & Mete 2010a). These factors include mother's characteristics, such as age (Emmanuel et al 2008), educational level (Lederman & Weis 2009), whether or not the pregnancy was planned (Visger 2013), employment status (Kiehl et al 2007), level of income (Lederman & Weis 2009) and social characteristics such as social support (Choi 2012;Mercer 2004; Serc ßekus ß & Mete 2010a) and family or spouse support (Lederman & Weis 2009). A study conducted in Turkey found that women who were highly educated, were employed, had a planned pregnancy, had knowledge about the pregnancy process, had a high income level and had social security adapted to pregnancy and IMR better than those who did not (Demirbas ß & Kadıo glu 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kiehl et al women’s adaptation to motherhood roles during pregnancy positively affects their self-confidence and life satisfaction in the postpartum period (2). A mother’s adaptation to pregnancy occurs through several stages, helping not only the mother to accept the pregnancy and its roles (3), but also strengthening the maternal-fetal attachment, which is important during both during pregnancy and in the postpartum period (4).…”
Section: Introductionmentioning
confidence: 99%